One or Many Antisexes? Introduction to Andrei Platonov’s “The Anti-Sexus” - Schuster, Aaron (Stasis, 2016)
This essay is intended as an introduction to Andrei Platonov’s short satirical brochure for a universal masturbation machine, titled “The Anti-Sexus.” I discuss some of the philosophical issues the pamphlet raises about capitalism and desire, death drive and satisfaction. Part of the trickiness of the text is that it is difficult to discern exactly who or what Platonov is lampooning. Is there a way to think about sexuality that avoids the alternatives of the invisible “handjob” of the market, revolutionary puritanism, and bureaucratic regulation? The essay makes connections between Platonov’s antisexualism and Viktor Shklovsky’s literary formalism, a more recent treatment of the same theme in Stanisław Lem, and Norbert Wiener’s apocalyptic cybernetics.